2006
DOI: 10.1080/13576280600984087
|View full text |Cite
|
Sign up to set email alerts
|

Career preference of final year medical students of Ziauddin Medical University

Abstract: The impact of the innovative community education programme is not clearly evident in the study, indicating that several other factors contribute towards decisions regarding career. A critical review by the university is required to strengthen the fields that are being overlooked by the students. A follow-up study would be beneficial to determine the changing trends in career preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 12 publications
7
53
1
3
Order By: Relevance
“…Existing data suggest that surgical careers are popular among Asian male medical students while obstetrics and gynecology is the popular choice among females. [1][2][3]5 This trend may be accounted by the fact that Asian countries in specific geographic regions share similar cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing data suggest that surgical careers are popular among Asian male medical students while obstetrics and gynecology is the popular choice among females. [1][2][3]5 This trend may be accounted by the fact that Asian countries in specific geographic regions share similar cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However "personal interest," and not lifestyle or social determinants, was ranked as the most influential factor. 3 An analogous study carried out in the Kingdom of Saudi Arabia (Table 1, 1.1.4) showed internal medicine, surgery, and pediatrics as the 3 career choices among final year medical students. Most of the male Saudi students chose surgery while obstetrics and gynecology and ophthalmology were the choices of career among female Saudi students.…”
Section: Global Trends For Surgical Career Selection (Table 1) Trendsmentioning
confidence: 93%
“…3 Medical career is unique as it is perceived to be very noble providing an opportunity to serve fellow human beings more than any other carrer. 4 The choice of a career in the medical field is a complex personal decision influenced by a multitude of factors.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the international studies done to address this issue have shown that the clinical subjects like Medicine, Surgery, Gynecology/Obstetrics and Pediatrics still continue to be the subjects of choice 2,3 . As medical science and technology become more sophisticated, the spotlight has been focused on specialties and super specialties 4 .…”
mentioning
confidence: 99%